Biochemical dehydrogenations of saccharides. VII. 2-Deoxy-D-gluconic acid from 2-deoxy-D-glucose - Kulhánek, M; Tadra, M; Linek, K; Kucár, S (Folia microbiologica, 1975)
Fermentation of a medium containing 5% 2-deoxy-D-glucose and barium carbonate by a strain of Pseudomonas aeruginosa yielded barium 2-deoxy-D-gluconate. The yield was 77% theoretical. The strain in question makes it possible to prepare directly calcium, magnesium, manganese and ferrous salts of 2-deoxy-D-gluconic acid. A treatment of 5% solution of 2-deoxy-D-glucose with commercial glucose oxidase preparation caused also a complete dehydrogenation.
Keywords: železo; Barium; Calcium; Deoxy Sugars; Salts; glukosaoxidasa; Deoxyglucose; fermentace; mangan; Iron; hořčík; soli; baryum; glukonáty; vápník; Gluconates; Pseudomonas aeruginosa; Glucose Oxidase; deoxycukry; Fermentation; Manganese; Cell-Free System; bezbuněčný systém; Magnesium; deoxyglukosa